A new pliosaurid from the Oxford Clay Formation of Oxfordshire, UK - HILARY F. KETCHUM; ROGER B.J. BENSON (Acta Palaeontologica Polonica, 2022)
We describe the anatomy of a new longirostrine pliosaurid, Eardasaurus powelli gen. et sp. nov., based on a substantially complete skeleton from the Middle Jurassic Oxford Clay Formation of Oxfordshire, UK. The specimen brings the number of pliosaurid genera known from the Oxford Clay Formation up to a minimum of six, contributing to our understanding of the most taxonomically rich pliosaurid assemblage. The teeth of Eardasaurus powelli gen. et sp. nov. have “carina-like” apicobasal enamel ridges, previously only identified in Liopleurodon ferox among Middle Jurassic pliosaurids, and which may be more widespread among early pliosaurids than has been recognised. Our phylogenetic analysis shows that Eardasaurus powelli gen. et sp. nov. is nested within Middle Jurassic thalassophonean pliosaurids, slightly more derived than Peloneustes philarchus, as sister to a group comprising “Pliosaurus” andrewsi, Simolestes vorax, Liopleurodon ferox, Pliosaurus spp. and brachauchenines.